-x × x = ? explain with solution
Answers
Answered by
1
-X ( X )= -X²
as,
x (x) = x²
and
- × + = -
so ur answeris -x²
kinda lame question
as,
x (x) = x²
and
- × + = -
so ur answeris -x²
kinda lame question
Answered by
1
Heya!
-x × x = -x²
All the three steps explained clearly with answer in the given picture
Hope it helps
@PoojaBBSR
-x × x = -x²
All the three steps explained clearly with answer in the given picture
Hope it helps
@PoojaBBSR
Attachments:
![](https://hi-static.z-dn.net/files/d96/7369e3ccffab96cc1326a2d18254d547.jpg)
![](https://hi-static.z-dn.net/files/d71/6bf7e25a455cf1b29a7f91fe8d78cf72.jpg)
![](https://hi-static.z-dn.net/files/d3d/3953f912b1915d28aa4dd360c18dd9b8.jpg)
![](https://hi-static.z-dn.net/files/d6e/88d6b8ba97569eb095c368533ce55d7e.jpg)
Similar questions